2018
DOI: 10.3390/ijms19113375
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of a Soluble γ-Chain Cytokine Receptor as a Regulator of IL-7-Induced Lymphoproliferative Disorders

Abstract: IL-7 is an essential, nonredundant growth factor for T and B cell generation and maintenance. While IL-7 deficiency results in lymphopenia, overexpression of IL-7 can cause neoplasia in experimental models. IL-7’s involvement in neoplasia has been appreciated through studies of IL-7 transgenic (Tg) mice models and human lymphoma patients. Since we recently found that a soluble form of the common γ-chain (γc) cytokine receptor (sγc) antagonistically regulates IL-7 signaling, IL-7 and sγc double-Tg mice were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…It is released by activated eosinophils and macrophages but also by endothelial and epithelial cells. Furthermore, it is implicated in diseases, such as atherosclerosis, in an independent manner from its action on eosinophils [34][35][36][37], as well as in CKD [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is released by activated eosinophils and macrophages but also by endothelial and epithelial cells. Furthermore, it is implicated in diseases, such as atherosclerosis, in an independent manner from its action on eosinophils [34][35][36][37], as well as in CKD [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although direct association analyses were not possible in STAT5 phosphorylation assays, we concluded that cytokine sensitivity of γ c high T-cell proportions promoted IL-2 (IL-15) rather than IL-7. Evidence for a role of differential γ c -dependent γ c cytokine signaling come from several animal models including experimental autoimmune encephalitis (EAE) and rheumatoid arthritis (25, 27, 3234). Hong et al assessed implications of the sγ c chain on cytokine signaling and found that this inhibitory variant especially blocked IL-2R signaling probably by binding to the IL-2Rß chain and preventing the association with membrane γ c proteins (27).…”
Section: Discussionmentioning
confidence: 99%